Inside Back Cover: Microfabrication Enables Quantification of Interfacial Activity in Thermal Catalysis (Small Methods 5/2021). Issue 5 (12th May 2021) - Frei, Matthias S.; Veenstra, Florentine L. P.; Capeder, David; Stewart, Joseph A.; Curulla‐Ferré, Daniel; Martín, Antonio J.; Mondelli, Cecilia; Pérez‐Ramírez, Javier
Abstract : In article number 2001231, Pérez‐Ramírez and co‐workers devise a method using microfabricated model catalysts and a custom‐designed reactor to decouple the contribution of metal‐oxide interfaces in Cu‐ZnO for methanol synthesis via CO and CO2 hydrogenation under process‐relevant conditions.